A survey of national, regional and hospital chief pharmacists on consultant pharmacist appointment strategy and performance in the united kingdom. Issue 2 (12th March 2012) - Howard, P.
Abstract : Background: Consultant pharmacists were introduced in hospitals in 2005 to provide the best care for patients and retain experienced pharmacists in practice. The framework stated that posts had to be approved at regional level, but local organisations should determine where they were required, and posts could be shared. Posts should provide expert practice, research and service development, education and professional leadership. Purpose: This survey aimed to identify the strategic approaches to planning new posts at all levels, barriers to appointment, assessment of current performance and improvements to current roles. Materials and methods: A SurveyMonkey was e-mailed to all the national, regional and Chief Pharmacists in the UK. Results: Responses were received from 70% of regional pharmacists and 73 Chief Pharmacists. Scotland, Northern Ireland and Wales were planning Consultant Pharmacists but currently had none in place. 44% of regions had a strategy for the appointment of new posts. Only 23% of Trust Chief Pharmacists had an agreed strategy for future appointments at regional level, 2% at local health economy level and 7% at Trust level. Both regional and Trust Chief Pharmacists identified a need for a strategy at local level (85% and 58% respectively), regional level: 65% and 50%, and national level 85% and 51%. The main barriers that prevented future appointments were finance, lack of transitional arrangements, insufficient funding for time at University, no need, and lack of quality applicants. 58% would part fund a post. Posts in planning were haemato-oncology, antimicrobials, critical care, renal, medicines safety and nutrition. Review of performance was good. Only 18% thought leadership was below expectation, 11% for education but 31% wanted more research. Trusts would like to bring more research funding in, whereas regions would like more research published. Conclusions: Consultant Pharmacists are generally delivering what their employers want. There needs to be a strategy for new posts at all levels.